Early clinical response to 5-fluorouracil 0.5% and salicylic acid 10% topical solution in the treatment of actinic keratoses of the head: an observational study. (4th July 2022) - Garofalo, Virginia; Geraci, Francesco; Di Prete, Monia; Lanna, Caterina; Lozzi, Flavia; Cosio, Terenzio; Lambiase, Sara; Gaeta Shumak, Ruslana; Di Raimondo, Cosimo; Diluvio, Laura; Bianchi, Luca; Campione, Elena
Abstract: Background: Actinic keratosis is one of the most common dermatological disorders. A new topical solution, constituted by 0.5% 5-fluorouracil and 10% salicylic acid (Actikerall, Almirall) has been introduced in the treatment pipeline of hyperkeratotic actinic keratoses of the head and neck. Patients and methods: We analyzed in an observational prospective clinical study the short-term treatment effectiveness of 5-fluorouracil and salicylic acid on face and scalp actinic keratoses of grade 1 and 2 of 40 patients. Efficacy assessment was performed by clinical dermatological examination, collecting color photographs, calculating AKASI score, and by means of dermoscopy for each target lesion at every visit. Results: AKASI score decreased from an initial score of 3.3 to a final score of 0.9. At week 4, we were able to record a complete clearance of 50% of the treated lesions and a partial clearance of 28%. At the end of 12 weeks, 84% of the total lesions showed complete clearance, while 8% had partial clearance. Conclusions: 5-fluorouracil and salicylic acid topical solution is effective in the treatment of mild to moderate actinic keratoses. In the future, further studies are needed to evaluate the chance of adjusting drug dosage according to patients' and actinic keratoses features.